Analysis of Fractional Schrödinger Equation Occurring in Quantum Mechanics (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we present Adomian decomposition method to solve linear fuzzy fractional integro-differential equation with fuzzy initial conditions. Results are compared with the results obtained using Fuzzy Laplace transform method.
Keywords: Fractioanl Schrödinger equaton; Modified Adomian decomposition method; Fractional partial differential equations